2017
DOI: 10.1007/s40336-017-0225-z
|View full text |Cite|
|
Sign up to set email alerts
|

Amino acid PET and MR perfusion imaging in brain tumours

Abstract: PurposeDespite the excellent capacity of the conventional MRI to image brain tumours, problems remain in answering a number of critical diagnostic questions. To overcome these diagnostic shortcomings, PET using radiolabeled amino acids and perfusion-weighted imaging (PWI) are currently under clinical evaluation. The role of amino acid PET and PWI in different diagnostic challenges in brain tumours is controversial.MethodsBased on the literature and experience of our centres in correlative imaging with PWI and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 158 publications
(167 reference statements)
1
33
0
2
Order By: Relevance
“…Our particular study design might also explain the lack of significant correlation between MET uptake and rCBV. Overall, we clearly demonstrate that MET PET has advantages over PWI, which is in line with previous studies [49,50], but in contrast to others [51].…”
supporting
confidence: 92%
“…Our particular study design might also explain the lack of significant correlation between MET uptake and rCBV. Overall, we clearly demonstrate that MET PET has advantages over PWI, which is in line with previous studies [49,50], but in contrast to others [51].…”
supporting
confidence: 92%
“…With regard to tumor uptake, L-amino acid radiotracers in general show remarkable advantages over their corresponding D-isomer due to the preference of amino acid transporters and related enzymes for the L-isomer. As such, most amino acid PET radiotracers currently used in the clinic are L-isomers 39,40 . However, at times, D-amino acid PET radiotracers display a similar tumor uptake as their L-counterparts and in some cases, have superior contrast performance to L-isomers due to their fast clearance from the blood pool [43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…It is common that the L-enantiomer of an amino acid PET tracer has higher tumor uptake than its D-counterpart 39,40 . Consistent with this, in breast cancer, it has previously been shown that L-and D-enantiomers of 1-[ 18 F]FETrp have different uptake profiles 33 .…”
Section: Specificity Of the 1-l-[ 18 F]fetrp Uptake In Medulloblastommentioning
confidence: 99%
“…However, the inherent limitation of high physiologic uptake in the normal brain tissue necessitates the search for other newer PET tracers. Although 13 Nammonia has a short half-life time, it is rapidly spreading in recent years because of its diagnostic power (perfusion-metabolism coupling tracer) and the easier interpretation for clinicians owing to the higher tumor to back-ground contrast compared to PWI and other PET tracers [31] . On the other hand, the short half-life time has the advantage of reducing the radiation.…”
Section: Discussionmentioning
confidence: 99%